AKTUALISASI MODERASI KEBERAGAMAAN DI LEMBAGA PENDIDIKAN BERCIRI ISLAM: Studi pada Sekolah Menengah Pertama (SMP) di Kabupaten Malang-Jawa Timur Indonesia - Dina Mardiana; M. Taufiqi Rahman (Universitas Tanjungpura, 2021)
The theme of religious moderation is increasingly important to study in line with the emergence of anxiety about strengthening intolerant, extremist, and radicalism-terrorism movements in several educational institutions in Indonesia. This research aims to examine the actualization of religious moderation values (read: Islamic moderation) of teachers at SMP Aisyiyah Boarding School and SMP Al-Irsyad Al-Islamiyyah Malang. Therefore, this research uses a qualitative approach to the type of case study research. Methods of data collection are carrying out through observation, in-dept interview, and documentation of the two research locus. At the same time, the data analysis used the interactive Miles-Huberman model. This results showed that teachers' religious moderation actualizes in two ways. First, the pathway formal-curriculum through the learning planning tools which are explicitly stated in the Learning Implementation Plan (RPP), as well as through extracurricular activities guided by teachers to students, namely scouts and student council; Second, is the pathways hidden-curriculum manifested in a pattern of habituation from teachers to students through an organizational culture that is run in schools, especially in the aspect of shared basic assumptions from the students